Application of Disciplinary Penalties - Stoicu, Narcisa Mihaela; Berlingher, Daniel; Creț, Daniela Cristina (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
Each branch of law acknowledges a specific form of liability. Therefore there are several forms of liability: disciplinary, civil, criminal, etc. These forms of legal liability are characterized by specific conditions of substance and form (way of establishment, embodiments, etc.). Therefore, the commission of an infringement determines the intervention of legal liability and the application of penalties. The penalty is a means to materialize liability and it will take its shape. In this scientific approach we intend to analyze the application of disciplinary penalties to civil servants.